2020
DOI: 10.1002/dvdy.242
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the rete testis during mouse embryonic development

Abstract: Background: The rete testis connects seminiferous tubules of the testis with efferent ducts having a mesonephric origin. The development of the rete testis is insufficiently studied, but there is evidence suggesting that it originates from gonadal cells. Here, the formation of the rete testis was investigated from E11.5 to E16.5 using immunofluorescent staining and 3D-modeling. Results: The rete testis became visible by SOX9 and PAX8 staining starting from E12.5. It was located in the mesonephros but connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…The technique allowed us to examine the anatomical distribution of the targeted cells in the intact gonad, by preserving the three-dimensional information. The evaluation was carried out at E13.5 when the rete structure develops, at E16.5, and at birth (P0) when testis and ovary development is well underway and rete formation is completed ( 19, 37 ). To this end, we labelled Pax8 -expressing cells and all their derivatives as well as Nr5a1 -expressing cells using a transgenic line Pax8:Cre;Rosa26:tdTomato;Nr5a1:GFP ( 7, 38, 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique allowed us to examine the anatomical distribution of the targeted cells in the intact gonad, by preserving the three-dimensional information. The evaluation was carried out at E13.5 when the rete structure develops, at E16.5, and at birth (P0) when testis and ovary development is well underway and rete formation is completed ( 19, 37 ). To this end, we labelled Pax8 -expressing cells and all their derivatives as well as Nr5a1 -expressing cells using a transgenic line Pax8:Cre;Rosa26:tdTomato;Nr5a1:GFP ( 7, 38, 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it remains unclear whether CE-derived progenitor cells contribute to other uncharacterized populations of the developing testis and ovary. Recent investigations leveraging transcriptomics, immunofluorescence and 3D reconstruction revealed that rete testis 3 precursors possess a dual molecular signature reflecting both a Sertoli (Sox9, Gata4, Wt1, Nr5a1) and a rete precursor (Pax8, Krt8 and Cdh1) identity, suggesting a common origin with the CE-derived supporting lineage (19)(20)(21)(22). The rete testis forms an essential bridging system connecting the seminiferous tubules with efferent ducts.…”
Section: Introductionmentioning
confidence: 99%
“…The rete ovarii (RO) is an epithelial appendage of the ovary thought to arise from the mesonephric tubules (Satoh, 1985). The RO was first described in 1870 by W. Waldeyer (as cited by Byskov and Lintern-Moore, 1973), and was believed to be a functionless female homologue of the male rete testis (Kulibin and Malolina, 2020; Wenzel and Odend’hal, 1985). It was once thought to degenerate in most individuals, however research shows that this structure persists into adulthood in large mammals (Archbald et al, 1971; Hadek, 1958; Mossman and Duke, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate the feasibility and value of whole embryo immunofluorescence to investigate tissue interactions and morphogenic relationships during development. Holistic data enables exploration of systems interactions which have not been captured in prior studies based on 3D reconstruction from serial sections of gonads (Brambell, 1927a;Kulibin and Malolina, 2020;Satoh, 1991;Wartenberg et al, 1991) and mesonephroi (Brambell, 1927b;Upadhyay et al, 1979;Vasquez et al, 1998aVasquez et al, , 1998b. Through contextualizing genital ridge development, we identified changes in the position of the early gonad within the embryo.…”
Section: Discussionmentioning
confidence: 99%